2021
DOI: 10.1111/jfb.14801
|View full text |Cite
|
Sign up to set email alerts
|

Notes on age determination, size and age structure, longevity and growth of co‐occurring macrourid fishes

Abstract: Nineteen species of the deep‐water fish family Macrouridae inhabit the Mid‐Atlantic Ridge (MAR) of the North Atlantic. Size and age structure, longevity and length at age were explored for seven of the more abundant species: Coryphaenoides armatus, Coryphaenoides brevibarbis, Coryphaenoides carapinus, Coryphaenoides guentheri, Coryphaenoides mediterraneus, Coryphaenoides rupestris and Macrourus berglax. The otoliths from these species had growth increments resembling those accepted as annuli in other deep‐wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We avoided exploring other models with more parameters because the WAIC penalizes them or because they do not have any biological significance (Richards, 1959;Katsanevakis, 2006). The continuous growth pattern observed in this study (as indicated by parameter estimates from the VBGF) and the representativeness of most age groups indicate that the round stingray completes its life cycle in the study area (Bergstad et al, 2021). Interestingly, the round stingray has been reported to segregate by size and life stage (Silva-Garay and Lowe, 2021), but there are no signs of segregation in our data set.…”
Section: Modelmentioning
confidence: 92%
“…We avoided exploring other models with more parameters because the WAIC penalizes them or because they do not have any biological significance (Richards, 1959;Katsanevakis, 2006). The continuous growth pattern observed in this study (as indicated by parameter estimates from the VBGF) and the representativeness of most age groups indicate that the round stingray completes its life cycle in the study area (Bergstad et al, 2021). Interestingly, the round stingray has been reported to segregate by size and life stage (Silva-Garay and Lowe, 2021), but there are no signs of segregation in our data set.…”
Section: Modelmentioning
confidence: 92%
“…Much of the information is related to C. armatus, mentioned as an abundant species living in deep habitats with maximum lengths over 87 cm total length (TL) and longevity of ca. 40 years (Iwamoto and Stein 1974;Yeh and Drazen 2011;Bergstad et al 2021). Hydrolagus melanophasma was reported in the southeastern Pacific on the last decade as part of catches in the Patagonian toothfish fishery (Bustamante et al 2012;Araya et al 2020;Alfaro-Shigueto et al 2022); however, its biological aspects remain unknown.…”
mentioning
confidence: 99%